Neuroprotective properties of extra virgin olive oil polyphenols in Alzheimer’s disease: a multi-target mechanistic review - Wei, Lin; Li, Zhenmin; Shi, Mingqin; Song, Wu; Teng, Zhanguo; Zhang, Chi (Frontiers in Nutrition, 2025)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder characterized by β-amyloid (Aβ) deposition, hyperphosphorylated tau protein, neuroinflammation, and mitochondrial dysfunction. The limited efficacy of single-target pharmacological strategies has spurred interest in multi-target therapeutic approaches. Extra virgin olive oil (EVOO), rich in diverse polyphenolic compounds, has emerged as a promising source of such multi-target neuroprotective agents. This review systematically elucidates the mechanisms of key EVOO polyphenols-hydroxytyrosol, oleuropein, tyrosol, verbascoside, oleocanthal, and ligustroside-in combating AD pathology. We highlight the growing body of evidence demonstrating that these polyphenols can synergistically inhibit the aggregation of Aβ and tau, mitigate neuroinflammation, restore mitochondrial function, reduce oxidative stress, and promote neurogenesis. Preclinical studies in cellular and animal models of AD consistently show that EVOO polyphenols can ameliorate cognitive deficits and pathological hallmarks. Future research should focus on validating these benefits in animals and clinical trials and developing optimized formulations for clinical application. In conclusion, the bioactive polyphenols in EVOO present a compelling multi-targeted therapeutic strategy with significant potential to delay the progression of AD by concurrently modulating multiple key pathological pathways.